Evaluating the role of cytokinesis-block micronucleus assay as a biomarker for oxidative stress-inducing DNA damage in type 2 diabetes mellitus patients - R. Vishakh; N. Suchetha Kumari; Adithi Bhandary; Shilpa S. Shetty; Prajna Bhandary; G. Tamizh Selvan (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Type 2 Diabetes Miletus (T2DM) is a common metabolic and lifestyle disorder leading to increased oxidative stress and DNA damage. The present study aims to evaluate the feasibility of utilizing the cytokinesis-block micronucleus assay (CBMN) as a biomarker for assessing the DNA damage induced due to variations in oxidative stress. Methodology The study group includes diabetic (n = 50) and non-diabetic (n = 50) subjects. The assays for the diabetes-like fasting blood sugar, postprandial glucose and hemoglobin A1c (HbA1c), lipid profiling, and serum ferritin level along with c-reactive protein (CRP) were applied. Further, the CBMN assay was performed to evaluate the micronuclei present in the lymphocytes of control and T2DM groups. Results Significant imbalance in the glycaemic index, dyslipidemia, increased ferritin levels, and CRP levels, with a significant increase of micronucleus frequency, was found in T2DM patients compared with the control group. Results suggest a trend of positive correlation between HbA1c and the micronuclei, indicating the assay’s potential importance as a biomarker for T2DM-induced risk assessment. Conclusion From the observed results, it can be suggested that the CBMN assay could be used to assess the risk of oxidative stress-induced DNA damage in high glycaemic index diabetic patients.